The pharmacology and therapeutic applications of monoclonal antibodies - María Sofía Castelli; Paul McGonigle; Pamela J. Hornby (Wiley, 2019)
Abstract Monoclonal antibodies (mAbs) have emerged as a major class of therapeutic agents on the market. To date, approximately 80 mAbs have been granted marketing approval. In 2018, 12 new mAbs were approved by the FDA, representing 20% of the total number of approved drugs. The majority of mAb therapeutics are for oncological and immunological/infectious diseases, but these are expanding into other disease areas. Over 100 monoclonal antibodies are in development, and their unique features ensure that these will remain a part of the therapeutic pipeline. Thus, the therapeutic value and the elucidation of their pharmacological properties supporting clinical development of these large molecules are unquestioned. However, their utilization as pharmacological tools in academic laboratories has lagged behind their small molecule counterparts. Early therapeutic mAbs targeted soluble cytokines, but now that mAbs also target membrane‐bound receptors and have increased circulating half‐life, their pharmacology is more complex. The principles of pharmacology have enabled the development of high affinity, potent and selective small molecule therapeutics with reduced off‐target effects and drug‐drug interactions. This review will discuss how the same basic principles can be applied to mAbs, with some important differences. Monoclonal antibodies have several benefits, such as fewer off‐target adverse effects, fewer drug‐drug interactions, higher specificity, and potentially increased efficacy through targeted therapy. Modifications to decrease the immunogenicity and increase the efficacy are described, with examples of optimizing their pharmacokinetic properties and enabling oral bioavailability. Increased awareness of these advances may help to increase their use in exploratory research and further understand and characterize their pharmacological properties.